Increase of the motility of buck semen with Andromed® extender and the addition of HTF (Agro Productividad, 2023)
Objective: To test whether HTF (Human Tubal Fluid) is capable of protecting goat sperm cells increasing the semen mObjective: To determine if HTF (Human Tubal Fluid) can protect buck sperm cells, increasing semen motility when used by itself or combined with the Andromed® commercial extender.Design/Methodology/Approach: The semen of eight bucks of the Boer breed was used (10 ejaculates per male). Each ejaculate was diluted in three treatments (5 repetitions per treatment): 1) only Andromed®; 2) only HTF; and 3) Andromed® + HTF. The following variables were evaluated: mass motility (MM) and progressive motility (MP) in fresh (37 °C) and refrigerated (5 °C) semen. The differences between treatments were detected, based on the MM and MP in fresh and refrigerated semen variables, using the GLM procedure (SAS V9). In the case of the MM evaluated in three different periods, the measures repeated over time were analyzed using the Proc Mixed procedure (SAS V9).Results: Regarding the quality of fresh spermatozoa, MM and MP recorded similar values (p>0.05) for the three treatments. On the one hand, MM registered 97.1% for Andromed®, 95.8% for HTF, and 97.5% for Andromed® + HTF; its highest value was achieved with the Andromed® + HTF combination, followed by Andromed® and HTF. On the other hand, the highest MP percentage was observed with the combination of Andromed® + HTF (91.0%), followed by Andromed® (90.4%), and HTF (89.0%). Regarding the quality of the sperm refrigerated at 5 °C, the combination of Andromed® + HTF had a higher MP value (p